BALANCING SECRECY AND TRANSPARENCY IN SMART CITIES: A SYSTEMATIC REVIEW OF BLOCKCHAIN-BASED GOVERNMENT DATA MANAGEMENT - Nabil Abdallh Abbas Almotawkel; Abdulrahman Mohammed Hussein Obaid (Jurnal Pilar Nusa Mandiri, 2026)
Blockchain offers a promising solution to recurring problems in centralized government data systems, including security vulnerabilities, inefficiencies, and declining public trust. Blockchain’s decentralized and tamper-resistant architecture provides a mechanism to balance transparency and confidentiality in the management of public data. This paper presents a systematic review of the application of blockchain technology in the government domain, evaluating its impact on data security, efficiency, and public participation. This systematic review was conducted following the PRISMA protocol and searched the Scopus database for publications from 2016 to 2025. Of the 592 publications retrieved, 49 met the eligibility and quality criteria. A thematic synthesis was conducted on the results with respect to transparency, confidentiality, governance, and scalability. The findings indicate that blockchain has the potential to enhance transparency and data security through the creation of tamper-resistant records that strengthen public oversight. Blockchain also has the potential to improve the efficiency of public service delivery through digital platforms such as land registry systems and health record management. However, challenges remain, particularly related to scalability and regulatory frameworks for the adoption and implementation of the technology. Therefore, adaptive regulatory frameworks and appropriate governance mechanisms are required to support fair and sustainable adoption of blockchain technology in government data management.